The efficacy of three metaldehyde pellets maketed in Argentina, on the control of Deroceras reticulatum (Muller) (Pulmonata: Stylommatophora - Salvio, C.=700 1 Faberi, A.J.; Lopez, A.N.; Manetti, P.L.
(Es, En)
Ilus., 31 ref.
Keywords: BABOSAS; PLAGAS DE PLANTAS; CONTROL DE PLAGAS; ATRAYENTES; METALDEHIDO; MOLUSCOCIDAS; EFICACIA; ESPAÑA; DEROCERAS RETICULATUM